Substantial reductions in ambient PAHs pollution and lives saved as a co-benefit of effective long-term PM2.5 pollution controls. (May 2018) - Kong, Shaofei; Yan, Qin; Zheng, Huang; Liu, Haibiao; Wang, Wei; Zheng, Shurui; Yang, Guowei; Zheng, Mingming; Wu, Jian; Qi, Shihua; Shen, Guofeng; Tang, Lili; et al.
Abstract: Under great efforts in fighting against serious haze problem of China since 2013, decreasing of air pollutants especially for fine particles (PM2.5 ) has been revealed for several key regions. This study tried to answer whether the reduction of PM2.5 -bound polycyclic aromatic hydrocarbons (PAHs) was coincident with PM2.5 because of long-term pollution control measures (PCM), and to assess source-oriented health risks associated with inhalation exposure to PAHs. Field measurements were carried out before and after the publishing of local air pollution protection plan for Nanjing, a mega-city in east China. Results indicated that the air quality was substantially improving, with a significant reduction in annual average PM2.5 by 34%, and moreover, PM2.5 -bound PAHs significantly reduced by 63% ( p < 0.001). The remarkable reduction was mainly attributable to the change of emission sources, compared to the influence of atmospheric circulation patterns, surface meteorological conditions, and atmospheric chemical reaction. Four PAHs sources including coal combustion (CC), petroleum and oil burning (PO), wood burning (WB) and vehicle emission (VE) were identified. On an annual basis, contributions to ambient PM2.5 -PAHs from WB, PO, CC and VE sources in the period before the action of control measures were 2.26, 2.20, 1.96 and 5.62 ng m −3, respectively. They reduced to 1.09, 0.37, 1.31 and 1.77 ng m −3 for the four source types, with the reduction percentages as 51, 83, 33 and 68%, respectively. The estimated reduction in lifetime lung cancer risk was around 61%. The study that firstly assessed the health effects of PAHs reduction as a co-benefit raised by air PCM sustained for a long period is believed to be applicable and referential for other mega-cities around the world for assessing the benefits of PCM. Highlights: A four-year campaign to evaluate PM2.5 -bound PAHs before and after strict air pollution control measures. Concentrations of PM2.5 -bound PAHs reduced higher than that of PM2.5 . The remarkable PAHs reduction was mainly attributable to the change of emission sources. Reduced cancer risk of PAHs was calculated, and corresponding sources were identified.